Tree Fodder Production to Bridging the Gap between the Need and Availability of Animal Fodder - Chanu, Thounaojam Bidya; Singh, Charan (Indian Forester, 2022)
Livestock provides sustenance to rural community by providing food security through supply of milk, meat and self-employment however additionally plays a vital role for poverty alleviation of farmers. The area under fodder trees and shrubs is meager and is less than one per cent of the total cultivated land. Presence of inferior and unproductive grass and tree species, lack of fertilization, absence of legume component, improper cutting and indiscriminate grazing are the factors accountable for poor productivity of the grasslands and tree lands. Thus, the present paper provides an insight into the fodder trees potentiality, constraints in its production, challenges and strategies to improve the productivity of grassland and tree lands. Promoting fodder tree planting in degraded and grazing lands facilitates to meet livestock needs for fodder and trees helps to alleviate degradation. Keeping in view the constraints in fodder production to beat the gap between demand and supply, the emphasis need to be given on various steps for augmenting the fodder production. Fodder production is a component of the farming system and efforts have to be made for increasing the forage production in a farming system approach.